The Diocesan Structure of Rus during the Mongol-Tatar Invasion in 1237–1240 (according to the chronicles) - Fomina T.Yu. (Золотоордынское обозрение)
Research objective: To analyze, on the basis of the chronicle sources, changes in the episcopal structure of Rus, which occurred during the campaign of the Mongol-Tatar troops of 1237–1240, and with the help of the historical-genetic method, characterize the process of the formation of relations between the Mongols and representatives of the ancient Russian church organization. Research materials: The article points to the debatable assessment of the impact of the Mongol-Tatar invasion on changes in the episcopal structure of the Kiev Metropolis. The emergence, transfer and liquidation of the ancient Russian episcopal centers actively took place before the first third of the 13th century. The article emphasizes the peculiarities of the position of Russian bishops during the Mongol offensive of 1237–1240. Chronicle sources report the devastation and plunder by the Horde troops of the Vladimir and Pereyaslav departments, while the Rostov, Chernigov and Galician bishops have retained their rank and material resources. As a result, the Russian church was freed from the payment of the Horde tribute, strengthened its influence on the all-Russian political processes, the clergy and church property were removed from the subordination of the princes. Results and novelty of the research: The use of the historical-genetic method made it possible to reveal the peculiarities of building up the relations of the Horde with representatives of the Russian episcopate. The laws of Yasa obliged the representatives of the Mongol Empire, and then the Golden Horde, with a high degree of tolerance to the representatives of the local clergy. The death of representatives of the Old Russian episcopate, recorded by chronicle sources, and the salvation of some of them, was directly related to the period of active hostilities, and after they ended, the fate of the clergy depended mainly on their loyalty to the Mongol power. Thus, the relationship of the Horde with representatives of the highest ecclesiastical hierarchy of Rus is not seen as so unambiguous, as it often appears in Russian historiography.